Impact of Intellectual Capital on Financial Performance (A Survey Study on the Banks Listed in Damascus Securities Exchange) - الشمالي, أحمد; ماهر الأمين; مريم عبد الحليم (Latakia University Journal - Economic and Legal Sciences Series, 2024)
This study aimed to determine the impact of intellectual capital on the financial performance of the 14 banks listed on the Damascus Securities Exchange during the period between 2016-2021 with a total of 84 observations, where data that serve the calculation of the research variables were collected from the financial statements published for banks on Damascus Securities Exchange website. Intellectual capital was measured through the Value Added Intellectual Coefficient (VAIC) model, which includes three components of intellectual capital: human capital efficiency, structural capital efficiency, physical capital efficiency, and financial performance measured by return on assets. The results showed that only two components of intellectual capital, human capital and physical capital, have a statistically significant positive impact on the financial performance of banks, unlike structural capital, where there is no statistically significant relationship between it and the financial performance of banks.